Lutein and Zeaxanthin Isomers Reduce Photoreceptor Degeneration in the Pde6brd10 Mouse Model of Retinitis Pigmentosa. (17th December 2018) - Yu, Minzhong; Yan, Weiming; Beight, Craig
Abstract : Purpose . Lutein, RR-zeaxanthin, and RS-zeaxanthin (L-Z) are antioxidants which can reduce endoplasmic reticulum stress (ERS) and oxidative stress (OS), and ameliorate neurodegenerative diseases. However, their treatment effect in the Pde6b rd10 ( rd10 ) mouse model of retinitis pigmentosa (RP) and the underlying cellular mechanisms have not been studied. ERS is an important factor which causes photoreceptor apoptosis. The aim of the current project is to test the treatment effect of L-Z in rd10 mice and to investigate the underlying molecular mechanisms of ERS. Methods . L-Z (Lutemax 2020, 10 mg/kg) diluted in sunflower oil (SFO, 1 mg/ml) or the same volume of SFO was administrated via gavage from postnatal day 6 (P6) to P20 daily in L-Z group (n=5) or SFO group (n=6) of rd10 mice. At P21, electroretinography (ERG) was performed to show the functional change of retinas. 78 kDa glucose-regulated protein (GRP78) and endoplasmic reticulum protein 29 (ERp29) were tested by western blot and immunostaining. Results . The ERG amplitudes were larger in the L-Z group than those of the SFO group in all flash luminances of dark-adapted and light-adapted ERG (all p < 0.01). Western blot revealed that GRP78 in the retinas of the L-Z group was significantly downregulated compared to that of the SFO group ( p < 0.01). Meanwhile, the retinal ERp29 protein was significantly upregulated in the L-Z treatment group than that of the SFO group ( p < 0.01). Conclusions . L-Z provide protection to the photoreceptors of rd10 mouse model of RP, which is probably associated with the reduction of ERS.